To study the effect of adding different levels of olive mill waste water mixture with cow manure at different degrees of anaerobic fermentation on some physical properties of soil and on Potato plant productivity. - ابراهيم جهاد; عيد هيثم; سلوم محمد (Latakia University Journal -Biological Sciences Series, 2021)
This research was carried out to study the effect of adding different levels of olive mill waste water mixture with cow manure at different degrees of anaerobic fermentation on some of the physical properties of heavy clay soil and its productivity of potato plants, the experiment included four levels of addition to the mixture from field capacity (0-2-4- 6) L / m2 and four degrees of anaerobic fermentation (0-10-20-40) day. The soil bulk density decreased in both depths (0-20cm) and (20-40 cm) with an increase in both the degree of fermentation and the level of addition and this decrease It was more pronounced at depth (0-20cm) than depth (20-40cm), especially at the first addition levels of all degrees of fermentation 2 L / m 2 and 4 L / m 2. It was also observed that the size of air pores larger than 10 microns and in depth (0-20cm) at the degree of fermentation was 40 days, and the percentage of addition was(6) L / m2 11.97% by volume compared to the control, and the level of addition did not play a role in increasing the percentage of these pores, but the largest role was For degrees of fermentation only, as for the depth (20-40cm), it was noted that its value increased with the increase in the level of addition at each degree of fermentation compared to the control, and the increase in the percentage of pores containing the water available to the plant was observed (0.2-10) microns and at depth (0- 20cm) affected by the increase in the level of addition and the degree of fermentation to reach its highest value at the level of addition 15% of the field capacity and the degree 40 days to (18.94)% by volume compared to the control, In terms of production, the level of addition 4 L/ m 2 at a degree of fermentation of 40 days anaerobically achieved the highest production, as production reached a significant increase of 68.8% compared to the control.